74‐2: Development of a Novel Reflective Display System with Multi‐primary Color for Digital Signage. Issue 1 (2nd June 2017) - Yata, Tatsuya; Tomizawa, Kazunari; Tamaki, Masaya; Sako, Kazuhiko; Nagatsuma, Toshiyuki; Nakamura, Kiyoshi; Harada, Tsutomu; Kabe, Masaaki
Abstract : We have developed four primary‐color reflective LCD and have improved yellow and red color saturation. The color gamut area of the developed LCD meets to the standard for printing (SNAP) which is defined for reproduction quality in newsprint production. The developed LCD has also a wide color gamut, wide operating‐temperature range and high‐quality moving images. It is suitable to realize future digital signage for outdoors.